Phosphoric acid pretreatment of poplar to optimize fermentable sugars production based on orthogonal experimental design - Chen, Deming; Tang, Wenjing; Wang, Hui; Sheng, Yequan; Tan, Xin; Shi, Yang; Fan, Wei; Ge, Shengbo (Frontiers in Chemistry, 2023)
The recalcitrant structure of raw poplar limited the production of fermentable sugars when it is applied as the material in the pretreatment of biochemical conversions. Phosphoric acid pretreatment was one efficient method to destroy the compact lignocellulose matrix. In this study, phosphoric acid pretreatment of poplar was optimized by an orthogonal experimental design to improve enzymatic digestibility. Based the orthogonal design, the effects of three factors in the phosphoric acid pretreatment, including reaction temperature, time duration, and phosphoric acid concentration were investigated with three different levels. The reason behind the choice of optimal condition could be well demonstrated by the variance of chemical compositions, hemicellulose removal ratio, and delignification of the woody material after pretreatment. According to the nine orthogonal pretreatments (L9(33)), pretreatment with the temperature of 190 °C, 150 min, 1.5%, v/v phosphoric acid concentration was proved to be the optimal condition. With this optimal condition, the enzymatic hydrolysis yield was improved to be 73.44%.